PENGARUH KUALITAS PELAYANAN, HARGA DAN NILAI PELANGGAN TERHADAP KEPUASAN PELANGGAN PENGGUNA JASA SERVIS BENGKEL AHASS 0002 SEMARANG HONDA CENTER - Lailia, Nimas; Suryoko, Sri; Saryadi, Saryadi (Jurnal Ilmu Administrasi Bisnis, 2013)
effort to keep relationships among customers, service quality is the key to maintain customers and give high value through customer’s value. Customers will compare between the services quality provided and price which is charged for servicing. The customers’ desired compatibility to the AHASS 0002’s will create customer satisfaction. This research aimed to find out the effect of service quality, price and customer value to customer satisfaction of AHASS 0002 Repair Shop Semarang Honda Center. The population in this research is the service customer users who served in AHASS 0002 Semarang Honda Center. The 100 respondents was taken as the research sample and the sampling technique used is the purposive sampling. Measurement scale using Likert scale. In data analysing using simple linear regression and multiple regression test helped with SPSS 16.00. Based on the results of data analysis, known that the service quality, price, and customer value has positive effect on customer satisfaction, either partially or simultaneously. Simultaneously, variable of service quality, price, and customer value affect on customer satisfaction at 69.5 percent. This means the better service quality, the suitable expected prices of the customers, the high value of customer, the high customer satisfaction.